Integrated management of Bromus diandrus in dryland cereal fields under no‐till. (30th April 2014) - García, A L; Royo‐Esnal, A; Torra, J; Cantero‐Martinez, C; Recasens, J; Fernandez‐Quintanilla, César
Summary As herbicides have limited effect in controlling Bromus diandrus in no‐till dryland cereal fields, the integration of chemical and cultural methods needs to be investigated. A field study was carried out in Lleida (Spain) during 2008–09, 2009–10 and 2010–11 seasons, in a no‐till winter cereal field integrating delayed crop sowing with herbicides in a barley–wheat–wheat rotation. Three crop sowing dates were considered: D1, mid‐October; D2, mid‐November; and D3, early December, and the herbicides mesosulfuron‐methyl plus iodosulfuron‐methyl‐sodium were applied in wheat. Weed density, cumulative emergence and fecundity were estimated for each sowing date. In all three seasons, a significant reduction in the cumulative emergence of B. diandrus as compared to D1 was observed in D2 (82.0, 97.5 and 98.1%) and D3 (80.8, 98.7 and 97.2%). In addition, a significant decrease in weed density and seed rain was observed across all sowing dates and seasons. The herbicide used in wheat was more effective under delayed sowing, due to lower weed density and presence of less developed weed seedlings. After three seasons, the populations of B. diandrus were completely depleted in D2 and D3. This study demonstrates the possibility of eliminating brome infestations in dryland cereal fields in no‐till systems through the integration of cultural and chemical strategies.